Peran Kelelahan Emosional Pada Pemediasian Work Life Balance Terhadap Kinerja Proyek Pada Software House di Wilayah Malang Raya - Uki Yonda Asepta; Krismi Budi Sienatra (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
The current work environment that is enacted is designed to have work interactions that have a positive impact on the personal life domain of employees and in particular they impact work-life balance. This research was conducted by examining the relationship between work life balance and project performance and emotional exhaustion as a mediation. The population in this study were software developer workers in Malang Raya with a total of 21 software houses. The sample technique uses non-probability, the number of respondents is 126 respondents. Data processing using SMART PLS 3.0 software. The results showed that emotional exhaustion had a significant negative effect on the project performance of professionals working in software development projects. Work-life balance has a significant negative effect on project emotional exhaustion of professionals working in software development projects. Work-life balance does not significantly affect the project performance of professionals working in software development projects. Emotional exhaustion perfectly mediates the effect of work life balance on the project performance.